Elza Furtado Gomide e a participação feminina no desenvolvimento da matemática brasileira no século XX - Santos, Arnaldo Aragão (2010)
This work points out the process of institutionalization of Brazilian Mathematics, more specifically in the Faculty of Philosophy, Sciences and Letters of the University of São Paulo through the academic career of Professor Elza Furtado Gomide. We have analyzed interviews, testimonials, and historical narratives by using a case study through an investigative approach of Oral History. Through this study we sought to ponder on the relationship between gender and science by considering Elza Furtado Gomide participation in the development of Mathematics in Brazil